Analysis of Factors Affecting Brand Loyalty to IOS Users In DKI Jakarta - Yona Aditya; Luwie Kosim; Innocentius Benarto (Enrichment : Journal of Management, 2021)
The purpose of this research is to evaluate the direct and indirect effects and impacts of Brand Experience, Brand Image, Brand Satisfaction, and Brand Loyalty on the perspectives of IOS operating system users in DKI Jakarta, specifically from the Four Stage Loyalty Model. The samples for this study were drawn from a total of 124 respondents who live in DKI Jakarta and are dispersed around the district (Central Jakarta, North Jakarta, East Jakarta, West Jakarta, and South Jakarta). The data was analyzed using the PLS-SEM (Partial Least Square Structural Equation Modeling) statistical tool, which also employs the SmartPls program tool after existing samples were acquired using a questionnaire distribution approach. The findings of this study conclude that Brand Experience has a favorable influence on Brand Image and Brand Satisfaction, as well as having an impact on Brand Loyalty for IOS users in DKI Jakarta, based on data processing and observations.